REAKSI PASAR MODAL INDONESIA SEBELUM DAN SESUDAH RESHUFFLE KABINET JILID III TAHUN 2022 - Wahyu Mahayoga, I Made; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023DO - 10.24843/EEB.2023.v12.i04.p16, 2023)
The Volume III 2022 cabinet Reshuffle is one of the non-financial events that will affect the Indonesian capital market. Therefore, the aim of this research is to test whether there are differences in average abnormal returns and business activity during the 2022 Volume III restructuring. The reaction of the Indonesian capital market during the observation period was studied through case studies. Method. The observation period was carried out three days before the announcement of the change in government Part III and three days after the announcement of the change in government Part III in 2022. The sample for this study was stocks listed on the LQ-45 Index. Secondary Data This study uses daily stock closing data, daily JCI and daily trading. There is a significant difference in the average abnormal rate of return before and after the Band III reform in 2022. There is no difference in the average trading volume before and after the 2022 volume III cabinet Reshuffle. Companies listed on the LQ-45 Index are encouraged to consider changes Volume III 2022 when considering the policy of national events to ensure that the public receives accurate and timely information about submitted index properties.